Towards equitable public sector plant breeding in the United States. Issue 6 (9th October 2022) - Brzozowski, Lauren; Hanson, Solveig; Jannink, Jean‐Luc; Meints, Brigid; Moore, Virginia; Tufan, Hale; Villwock, Seren
Abstract: Plant breeding is central to agriculture and shifts in plant breeding practices (e.g., hybrid development) and selection goals (e.g., response to synthetic fertilizer) have catalyzed monumental and persistent changes in agricultural production systems of all scales with social, political, economic, and environmental repercussions. Although plant breeders are largely trained in the sciences of biology, genetics, and statistics, we posit an ethical imperative to examine the degree of equity with which the benefits of new research and plant cultivars are distributed. In the United States, the history of plant breeding parallels the colonial history of agriculture, which compels reflection by current plant breeders about their role in shaping our agricultural system. In this perspective essay, we examine longstanding ideas about equitable food systems through the lens of public plant breeding in the United States. We propose a framework for equitable plant breeding with respect to both its process and outcomes, and we intend for the ideas presented herein to catalyze reflection, discussions, and actions as the plant breeding community seeks greater equity in the food and seed systems our work supports. Core Ideas: How does public plant breeding research contribute to equity in agriculture and society? The authors call for an examination of both the processes and outcomes of plant breeding. There is a need for expanding plant breeding training to include equity competencies. The authors call for reflection and discussion within and beyond the plant breeding community.